Maldives : 2010 Article IV Consultation: Staff Report; Staff Statement and Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Maldives. (IMF Staff Country Reports; Country Report, 2011)
Owing to severe fiscal and external imbalances, the Maldives government adopted an IMF program in 2009. Despite some crucial initial actions, fiscal slippages and political polarization have undermined the restoration of sustainability. The key policy challenge is to prevent a fiscal crisis, achieve macroeconomic sustainability, and stimulate growth. The authorities concur with the need to tighten monetary policy. The authorities have welcomed the IMF program as a useful framework to guide and reinforce their efforts to restore external balance and fiscal sustainability.